STORAGE STRUCTURE OF MEASURING SYSTEM SIGNALS FOR HIGH ACCURACY ROPE DEFECTOSCOPE - Strelkov, M.A. (Perm Federal Research Centre Journal, 2015)
The article describes the structure for compact data storage in RAM and flash-memory that provides fail-safe back up and information transfer over Bluetooth.